CNS disease models with human pluripotent stem cells in the CRISPR age. (December 2016) - Muffat, Julien; Li, Yun; Jaenisch, Rudolf
Highlights: Pluripotent stem cells can be engineered to carry disease-relevant genetic variants. Stem cells can be differentiated into all relevant brain cells, including microglia. Brain development is modeled in self-assembling suspended organoids. More organotypic neuro-glial interactions are modeled in reaggregated 3D cultures. Perfusion of defined medium through 3D cultures may replicate brain homeostasis. Abstract : In vitro differentiation of human pluripotent stem cells provides a systematic platform to investigate the physiological development and function of the human nervous system, as well as the etiology and consequence when these processes go awry. Recent development in three-dimensional (3D) organotypic culture systems allows modeling of the complex structure formation of the human CNS, and the intricate interactions between various resident neuronal and glial cell types. Combined with an ever-expanding genome editing and regulation toolkit such as CRISPR/Cas9, it is now a possibility to study human neurological disease in the relevant molecular, cellular and anatomical context. In this article, we review recent progress in 3D neural culture and the implications for disease modeling.